Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2166/wst.2014.477
|View full text |Cite
|
Sign up to set email alerts
|

LCA applied to elucidate opportunities for biogas from wastewaters in Colombia

Abstract: Biogas produced in municipal and industrial wastewater treatment facilities (BWWF) is a resource wasted in several socio-economic contexts. BWWF-based projects are compared against energy projects using conventional electricity or natural gas (NG), following strict economic considerations that usually tip the balance in favour of conventional energy supply. This is because the economic gain associated with the environmental benefits of using small biogas sources like BWWF does not overcome the technical and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Europe (e.g. Mahgoub et al, 2010;Roushdi et al 2012;Meneses-Jácome et al, 2015;Wang et al, 2015;Lu et al, 2017) or Japan (Limphitakphong et al, 2016)) have been used due to the absence of more specific information. Moreover, Kalbar et al (2013Kalbar et al ( , 2014 and…”
Section: Use Of Normalization and Weightingmentioning
confidence: 99%
“…Europe (e.g. Mahgoub et al, 2010;Roushdi et al 2012;Meneses-Jácome et al, 2015;Wang et al, 2015;Lu et al, 2017) or Japan (Limphitakphong et al, 2016)) have been used due to the absence of more specific information. Moreover, Kalbar et al (2013Kalbar et al ( , 2014 and…”
Section: Use Of Normalization and Weightingmentioning
confidence: 99%
“…The AD stage includes the transport of the sorted FW by municipal waste collection vehicles to the treatment plant, which is assumed to be located just beside the Mondonedo landfill with an estimated distance of 30 km (round trip), similarly to the one reported for the Colombian geography at [9]. The AD plant consists of 5 sets of 2 biodigesters in series -with the sets in parallel -each with a working volume of 7000 m 3 .…”
Section: Life Cycle Inventorymentioning
confidence: 99%
“…An electrical efficiency of 38 % and 46 % for thermal energy, a methane's low heating value (LHV) of 10 kWh/m 3 and a capacity factor of 8030 h/year have been assumed considering values reported in [9], [37]. The modelled installed capacity (2 MW) fits the requirements to produce the calculated electricity and heat outputs of 10 318 and 12 490 MWh/year, respectively (before losses and meeting internal demands).…”
Section: Environmental and Climate Technologies _____________________...mentioning
confidence: 99%
See 1 more Smart Citation
“…Schütze et al [24] made a comparative evaluation of four commercially available treatment plant simulation tools and concluded that out of the four programs under investigation (BIOWIN ® , ESP ® , GPS-X ® , and STOAT ® ), GPS-X ® was the one most closely meeting the requirements defined by the water company. Apart from its implementation in real-scale plants for optimization and control purposes, it has been widely used as a tool for analysis of the performance of wastewater treatment plants in a number of published papers that demonstrate the potential use of this software [27] to simulate nutrient removal processes in WWTP [25,[28][29][30], as well as to simulate anaerobic digestion [31][32][33][34]. However, for energetic and economic considerations, a more generalized software called SuperPro ® v.2.7 [35] was successfully implemented in a wide range of industries such as biopharmaceutical [36,37], cellulosic ethanol [38], biodiesel [39], and bioenergy systems [40,41]; thus, it was selected for energetic calculations of the scenarios studied in the present work.…”
Section: Introductionmentioning
confidence: 99%